Pharmacokinetics and Bioequivalence of 2 Tablet Formulations of Olanzapine in Healthy Chinese Volunteers: a Randomized, Open-Label, Single-Dose Study - Chen, Q.; Zhang, M.-q.; Liu, Y.; Liu, Y.-m.; Li, S.-j.; Lu, C.; Liu, G.-y.; Qi, Y.-l.; Yu, C.; Jia, J.-y. (Arzneimittelforschung, 2012)
Olanzapine is a widely used agent for the treatment of schizophrenia.The aim of this study was to evaluate bioequivalence of two 10-mg tablet formulations of olanzapine following single oral dose in adult male volunteers.This was a randomized, single-dose, open-label, crossover bioequivalence study. Plasma samples were collected before dosing and at 0.5, 1.0, 1.5, 2.0, 3.0, 4.0, 5.0, 6.0, 8.0, 12.0, 24.0, 36.0, 48.0, 72.0, 96.0, 120.0 and 144.0 h after dosing. Plasma concentrations of olanzapine were determined by using a liquid chromatography-tandem mass spectrometric (LC-MS/MS) method. Statistical analysis of the pharmacokinetic parameters Cmax, AUC0–144, and AUC0–∞ was conducted to determine bioequivalence. Adverse events were monitored, recorded and evaluated by investigators throughout the study.24 healthy male Chinese volunteers between the ages of 18–40 years with a body mass index (BMI) between 19 and 24 kg/m2 were enrolled in the study. The mean (SD) Cmax, AUC0–144, and AUC0–∞ values after administration of the test and reference formulations, respectively, were as follows: 18.91 (5.320) vs. 18.44 (4.758) ng/mL, 582.9 (118.23) vs. 587.3 (127.12) ng/mL · h, and 615.4 (131.39) vs. 615.8 (137.45) ng/mL · h. The 90% CIs for the ratios of AUC0–144 and Cmax were 96.9% to 102.4% and 93.7% to 110.2%, respectively. The relative bioavailability of the test formulation to reference formulation was 100.1%. Both formulations were generally well tolerated and no serious AEs were reported in the study.The 90% CIs for the ratios of mean Cmax, AUC0–144, and AUC0–∞ met the regulatory criteria for bioequivalence.
Keywords: olanzapine; bioequivalence; pharmacokinetics; LC-MS/MS; adverse events